Immediate brain plasticity after one hour of brain–computer interface (BCI) - Nierhaus, Till; Vidaurre, Carmen; Sannelli, Claudia; Mueller, Klaus‐Robert; Villringer, Arno (The Journal of physiology, 2021)
Key points Two groups of inexperienced brain‐computer interface users underwent a purely mental EEG‐BCI session that rapidly impacted on their brain. Modulations in structural and functional MRI were found after only 1 h of BCI training. Two different types of BCI (based on motor imagery or visually evoked potentials) were employed and analyses showed that the brain plastic changes are spatially specific for the respective neurofeedback. This spatial specificity promises tailored therapeutic interventions (e.g. for stroke patients). A brain‐computer‐interface (BCI) allows humans to control computational devices using only neural signals. However, it is still an open question, whether performing BCI also impacts on the brain itself, i.e. whether brain plasticity is induced. Here, we show rapid and spatially specific signs of brain plasticity measured with functional and structural MRI after only 1 h of purely mental BCI training in BCI‐naive subjects. We employed two BCI approaches with neurofeedback based on (i) modulations of EEG rhythms by motor imagery (MI‐BCI) or (ii) event‐related potentials elicited by visually targeting flashing letters (ERP‐BCI). Before and after the BCI session we performed structural and functional MRI. For both BCI approaches we found increased T1‐weighted MR signal in the grey matter of the respective target brain regions, such as occipital/parietal areas after ERP‐BCI and precuneus and sensorimotor regions after MI‐BCI. The latter also showed increased functional connectivity and higher task‐evoked BOLD activity in the same areas. Our results demonstrate for the first time that BCI by means of targeted neurofeedback rapidly impacts on MRI measures of brain structure and function. The spatial specificity of BCI‐induced brain plasticity promises therapeutic interventions tailored to individual functional deficits, for example in patients after stroke. Key points Two groups of inexperienced brain‐computer interface users underwent a purely mental EEG‐BCI session that rapidly impacted on their brain. Modulations in structural and functional MRI were found after only 1 h of BCI training. Two different types of BCI (based on motor imagery or visually evoked potentials) were employed and analyses showed that the brain plastic changes are spatially specific for the respective neurofeedback. This spatial specificity promises tailored therapeutic interventions (e.g. for stroke patients).